FEATURES OF CHROMIUM DOPING OF WEAR-RESISTANT CAST IRON - V. V. Netrebko; I. P. Volchok (Литьë и металлургия, 2013)
The aim of this work analysis of the influence of chromium on the process of carbide formation, changes in chemical composition of the metal substrate in the areas adjacent to the carbides and at the hardness of iron while economy nickel and manganesealloying.